2020
DOI: 10.1021/acs.jpcc.0c05786
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of NaGdF4:Er3+/Yb3+ Upconversion Particles as Exogenous Contrast Agent for Swept-Source Optical Coherence Tomography: In Vitro Animal Tissue Imaging

Abstract: Swept-source optical coherence tomography (SSOCT) is a noncontact, noninvasive bioimaging tool that uses various probes to obtain high contrast images. Rare-earth based upconversion particles (UCPs) provide a unique platform to enhance the capabilities of bioimaging techniques. The UCPs can act as contrast enhancers for the SSOCT with additional optical functionality, and hence in this work upconversion emission optimized polyvinylpyrrolidone (PVP)/NaGdF4:Er3+/Yb3+ UCPs were synthesized and then injected into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…It has been reported that “n” deviates as the competition between linear decay and the UC process increases [10a] hence for the two‐photon process n=/∼2 and “n” becomes equal to or <1 for the single‐photon process. As shown in Figure S13a,b, the number of photons involved in the green and red emissions of the UCB and UCN are found to be 1.42, 0.85, and 1.32, 0.83 respectively which are in agreement with the literature [1e,10a,24] . Yet, the negligible variation of “n” among both the materials indicates a similar chemical environment of Er 3+ , Yb 3+, and their statistical distribution in the lattice.…”
Section: Resultssupporting
confidence: 81%
“…It has been reported that “n” deviates as the competition between linear decay and the UC process increases [10a] hence for the two‐photon process n=/∼2 and “n” becomes equal to or <1 for the single‐photon process. As shown in Figure S13a,b, the number of photons involved in the green and red emissions of the UCB and UCN are found to be 1.42, 0.85, and 1.32, 0.83 respectively which are in agreement with the literature [1e,10a,24] . Yet, the negligible variation of “n” among both the materials indicates a similar chemical environment of Er 3+ , Yb 3+, and their statistical distribution in the lattice.…”
Section: Resultssupporting
confidence: 81%
“…The bands present at 733 cm À1 , 2856 cm À1 , and 2928 cm À1 can be assigned to the rocking vibration and the symmetric and asymmetric stretching of the CH 2 molecule of oleic acid, respectively. 25,29 This confirms the coating of oleic acid on the surface of the UCNPs. The band present at 1119 cm À1 is due to the C-O stretching of an alcohol group like ethanol.…”
Section: Fourier-transform Infrared (Ftir) Spectroscopysupporting
confidence: 62%
“…23 Mohan et al synthesized NaYF 4 :Ho 3+ /Yb 3+ phosphors and reported contrast enhancement in OCT-based imaging, but since the particle size was larger and agglomerated due to the synthesis method adopted, the particles were not able to diffuse efficiently into the cell; hence the contrast and depth resolution were limited. 24 In our previous reports, UCNPs were studied as a contrast enhancer for OCT. 25,26 Maurya et al 25 for the first time showed that an NaGdF 4 :Er 3+ /Yb 3+ upconversion phosphor has the capacity to enhance OCT image contrast through enhanced scattering of OCT scanning radiation by excited phosphor particles. The upconversion sample they prepared was not well dispersible in liquid media due to the synthesis methodology adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Notably, lanthanide-doped UCNPs have certain significant advantages, including high chemical stability, good photostability, zero autofluorescence background and low toxicity. [16][17][18] Based on this, UCNPs have become an efficient candidate in the analysis of biological and environmental samples, especially for luminescence imaging. [19][20][21] Total internal reflection (TIR) imaging technology could use an evanescent wave to excite fluorescent molecules in the range of hundreds of nanometers on the sample surface, 22,23 and is emerging as an extremely powerful tool used in single particle imaging.…”
Section: Introductionmentioning
confidence: 99%